An empirical measure of the rate of white dwarf cooling in 47 tucanae - Goldsbury, Ryan; Tremblay, Pier-Emmanuel (The astrophysical journal, 2012)
We present an empirical determination of the white dwarf cooling sequence in the globular cluster 47 Tucanae. Using spectral models, we determine temperatures for 887 objects from Wide Field Camera 3 data, as well as 292 objects from data taken with the Advanced Camera for Surveys. We make the assumption that the rate of white dwarf formation in the cluster is constant. Stellar evolution models are then used to determine the rate at which objects are leaving the main sequence, which must be the same as the rate at which objects are arriving on the white dwarf sequence in our field. The result is an empirically derived relation between temperature ( T eff ) and time ( t ) on the white dwarf cooling sequence. Comparing this result to theoretical cooling models, we find general agreement with the expected slopes between 20,000 K and 30,000 K and between 6000 K and 20,000 K, but the transition to the Mestel cooling rate of T eff ##IMG## [http://ej.iop.org/icons/Entities/vprop.gif] vprop t -0.4 is found to occur at hotter temperatures, and more abruptly than is predicted by any of these models.